Comparison of Gender schemas of Couples in women with and without Spouse abuse referred to Health Care Centers in Mashhad in 2015 - Shahla Nourani Saadoldin; Somayyeh Baharshahi; Habibollah Esmaily; Negar Asghari Pour (Mashhad University of Medical Sciences, 2017)
Introduction: Spouse abuse refers to violence which is occurred or is being occurred from the partner. Gender role schemas is a set of one's beliefs about male or female identity, so it can affect the people's relationships. This study was performed with aim to compare the gender schemas couples in women with and without spouse abuse referred to health care centers in Mashhad. Methods: This analytical-comparative study was performed on 257 couples referred to Mashhad health care centers in 2015. The tools included: Bem`s Sex-Role Inventory and ISA questionnaire (Index Spouse Abuse). By using ISA questionnaire, the couples were divided into two groups of with and without Spouse abuse, and using Bem questionnaire, the scores of femininity, masculinity and undifferentiated in women and men were determined. Data were analyzed by SPSS software (version 16), and Chi-square, Fisher, independent-t and Mann-Whitney tests. P<0.05 was considered significant. Results: Mean scores of femininity and masculinity in men without spouse abuse were significantly higher than other group (P=0.015) (P=0.013). Mean score of undifferentiated in men without spouse abuse was significantly lower than other group (P=0.024). Conclusion: Femininity attributes along with masculinity attributes in men decrease spouse abuse. But undifferentiated attributes in men are considered as risk factor for spouse abuse.